2016
DOI: 10.1108/jkm-05-2016-0203
|View full text |Cite
|
Sign up to set email alerts
|

Understanding counterproductive knowledge behavior: antecedents and consequences of intra-organizational knowledge hiding

Abstract: Purpose This paper aims to explore antecedents and consequences of intra-organizational knowledge hiding. Design/methodology/approach A model was developed and tested with data collected from 691 knowledge workers from 15 North American credit unions. Findings Knowledge hiding and knowledge sharing belong to unique yet possibly overlapping constructs. Individual employees believe that they engage in knowledge hiding to a lesser degree than their co-workers. The availability of knowledge management systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
522
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 389 publications
(542 citation statements)
references
References 132 publications
(124 reference statements)
13
522
3
4
Order By: Relevance
“…In the workplace, organizational identification is the primary factor shaping employees' attitudes and cooperative behaviors within groups (Blader & Tyler, ). Organizational identification has the potential to decrease employees' counterproductive knowledge behaviors, such as knowledge hiding, by enabling them to judge whether their conduct is congruent with the interests of their organizations (Ashforth & Mael, ; Mael & Ashforth, ; Serenko & Bontis, ). Employees with strong organizational identification may think about issues in terms of organizational interests and strive to achieve group accomplishments (Dutton, Dukerich, & Harquail, ; Hogg & Terry, ; Tse et al, ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the workplace, organizational identification is the primary factor shaping employees' attitudes and cooperative behaviors within groups (Blader & Tyler, ). Organizational identification has the potential to decrease employees' counterproductive knowledge behaviors, such as knowledge hiding, by enabling them to judge whether their conduct is congruent with the interests of their organizations (Ashforth & Mael, ; Mael & Ashforth, ; Serenko & Bontis, ). Employees with strong organizational identification may think about issues in terms of organizational interests and strive to achieve group accomplishments (Dutton, Dukerich, & Harquail, ; Hogg & Terry, ; Tse et al, ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…This phenomenon is called knowledge hiding (Connelly et al, ). Accordingly, scholars have shown great interest in knowledge hiding (Černe, Hernaus, Dysvik, & Škerlavaj, ; Černe, Nerstad, Dysvik, & Škerlavaj, ; Connelly et al, ; Kumar Jha & Varkkey, ; Serenko & Bontis, ). Prior research has indicated the harmfulness of knowledge hiding, such as destructing creativity (Černe et al, ; Černe et al, ), impeding the transmission and development of new knowledge (Černe et al, ), and increasing turnover intention (Connelly et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This open communication can even have positive effects on the social relationship (Connelly & Zweig, ). Individuals who use EH and PD will therefore perceive and expect their strategies as more socially harmful than RH, will react with stronger negative effects on job satisfaction, and increased levels of turnover intentions (Ashforth & Mael, ; Edwards, ; Serenko & Bontis, ). RH is less clear: The behavior can be openly justified as honest and more cooperative (e.g., Gordon & Miller, ; Wojciszke, ), such that knowledge seekers and hiders do not consider it deceptive.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Knowledge hiding which refers to an intentional attempt to conceal or withhold knowledge that is requested by others [2], is deemed as one counterproductive knowledge behavior [10]. However, thus far, few research have examined the relationship between individual personality and knowledge hiding [1] [7].…”
Section: Introductionmentioning
confidence: 99%